2016
DOI: 10.1016/j.reth.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic cultivation with radial flow bioreactor enhances proliferation or differentiation of rat bone marrow cells by fibroblast growth factor or osteogenic differentiation factor

Abstract: Dynamic cultivation using a radial flow bioreactor (RFB) has gained increasing interest as a method of achieving bone regeneration. In order to enhance bone generation in large bone defects, it is necessary to use an RFB to expand the primary cells such as bone marrow cells derived from biotissue. The present study aimed to evaluate the cell expansion and osteogenic differentiation of rat bone marrow cells (rBMC) when added to basic fibroblast growth factor containing medium (bFGFM) or osteogenic differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Basic FGF (bFGF), is a potent mitogen for MSCs (Martin, Muraglia, Campanile, Cancedda, & Quarto, ), which resulted in incorporation of a higher number of osteocytes into healing bone when treated with bFGF (Kawaguchi et al, ). Kanda et al (). reported that culture of the rat bone marrow cells (rBMC) in bFGF containing medium resulted in a significant increase in cell number and cell expansion, as well as expression of the BMP‐2 and osteopontin.…”
Section: Introductionmentioning
confidence: 99%
“…Basic FGF (bFGF), is a potent mitogen for MSCs (Martin, Muraglia, Campanile, Cancedda, & Quarto, ), which resulted in incorporation of a higher number of osteocytes into healing bone when treated with bFGF (Kawaguchi et al, ). Kanda et al (). reported that culture of the rat bone marrow cells (rBMC) in bFGF containing medium resulted in a significant increase in cell number and cell expansion, as well as expression of the BMP‐2 and osteopontin.…”
Section: Introductionmentioning
confidence: 99%
“…Alkaline phosphatase (ALP), as an early marker for osteogenic differentiation, was used as an indicator of osteoblastic mineralization . As shown in Figure a, the ALP activities of the osteoblasts were evaluated on days 7 and 14 on Ta­(B), Ta40, and Ta70 cultured with MC cells.…”
Section: Resultsmentioning
confidence: 99%
“…Alkaline phosphatase (ALP), as an early marker for osteogenic differentiation, was used as an indicator for osteoblastic mineralization. 53 As shown in Figure 7(a), the ALP activity of the osteoblasts were evaluated at days 7 and 14 on Ta(B), Ta40 and Ta70 cultured with MC cells. The ALP activity on bulk Ta(B) at day 7, was lower than those of two nanolamellar Ta surfaces, and the activity on Ta70 was the highest.…”
Section: Methodsmentioning
confidence: 99%
“…Interstitial fluid flow modulates osteogenesis and can be recapitulated in vitro at the milliscale level through the generation of fluid shear stress or through the application of mechanical strains ( Alfieri et al, 2019 ; Ramani-Mohan et al, 2018 ), by using both commercially available and custom-made perfusion bioreactors ( Tseng et al, 2014 ; Kleinhans et al, 2015 ; Kanda et al, 2016 ; Beşkardeş et al, 2018 ; Burgio et al, 2018 ; Ramani-Mohan et al, 2018 ; De Luca et al, 2020 ). U-Cup bioreactors are the most widely used among those offered by the market, as they effectively perfuse media into the scaffold through a pump system.…”
Section: Mimicking and Studying The Biological Features Of Bone Microenvironment By Using Perfused Macro/milli/micro Bioreactorsmentioning
confidence: 99%